Legal Analysis of the Use of Deed de Command as a Supporting Basis for Collateral Execution - Liang Ning, Ni Luh Nita Mey; Mahendrawati, Ni Luh Made; Renaya, Nengah (Journal of Law, Politic and Humanities, 2025)
This article examines the Legal Analysis of the Use of Deed of Command as a Supporting Basis for Collateral Execution. The object of this research is the practice of using Deed De Command in the execution of collateral by creditors. The purpose of this study is to evaluate the legality, validity, and effectiveness of the use of Deed De Command in supporting the execution of collateral and its impact on creditor risk management. The research method used is normative law with descriptive analysis. The results of the study show that the Deed De Command has an important role in accelerating the execution of collateral and reducing Non-Performing Loans, although there is a gap in the norms in the regulations governing the use of the deed, which can cause legal uncertainty. In conclusion, the De Command Act is very relevant in accelerating the settlement of non-performing loans, but there needs to be regulatory updates to ensure legal certainty in its implementation